Correction of Risk Estimates for Measurement Error in Epidemiology - Bashir, S. A.; Duffy, S. W. (Methods of Information in Medicine, 1995)
Epidemiologists are under considerable pressure to acknowledge the presence of measurement error in the determination of risk factors. Repeatability and validation studies are often prescribed in conjunction with epidemiological studies. We describe some practical uses for repeatability and validation study data, in terms of correcting risk estimates for measurement error. Commonly available methods are described, with their advantages and shortcomings. A user-friendly computer program to carry out the analyses described accompanies the paper.
Keywords: Epidemiology; Risk Factors; Measurement Errors